The perioperative management of caesarean section related haemorrhage in a material near-miss population: a retrospective study - Iputo, Rebecca Atebat (My University, 2021)
Background: Maternal near-miss (MNM) is a risk stratification classification for maternal morbidity. The purpose of this study was to describe perioperative care used in the management of this population of women who have undergone caesarean section (CS). Methods: This was a retrospective, descriptive study at a single tertiary institute over a 1-year period in Johannesburg. Patients enrolled into the study were women who were classified as MNMs who had undergone a CS and had blood loss ≥ 1000 ml during or after delivery. Results: The primary outcome was the MNM rate for CS deliveries. The median age was 28, with a median parity of 2 (44%), and overall estimated blood loss volume of 1800 ml. The leading cause of haemorrhage was postpartum haemorrhage (87%). Eighteen (17%) of the subjects had a relook surgery for postpartum CS sepsis. Perioperative risk factors for haemorrhage were: parity of 3 (p = 0.0185), first (index) CS, antepartum haemorrhage, and multiple interventions to arrest haemorrhage (p < 0.001 for all). Management factors associated with blood loss (p < 0.001) included a massive transfusion, tranexamic acid use, and a B-Lynch surgical intervention. Management included uterotonic drugs, transfusion blood products, and surgical intervention. Conclusions: Postpartum haemorrhage was the leading cause of haemorrhage and was aggravated by the presence of antepartum haemorrhage. These patients often require multiple interventions. Future studies should develop a severity scoring index to better identify women at risk, on hospital admission
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in the partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology, 2021